DE AMICITIA EN ROMA: LA TRADICIÓN CICERONIANA (Stylos, 2020)
In this paper, Cicero’s De amicitia is analyzed in order to underline, first of all, the contribution Roman philosophy makes to a subject rooted in Greek thought. It considers the ways, properly philosophical, in which this subjects is addressed in Cicero’s practical philosophy, from the perspective of his writings, especially De Republica, De legibus, De finibus, which come before De amicitia. The author of this paper deals with central elements of ciceronian finalism in its own main traits, as well as the teleological cosmology and the anthropological philosophy entailed in Cicero’s De amicitia, considering mainly the axe natura-amicitia.
Keywords: Cicero; amicitia-natura; amicitia-ratio; amicitia-virtus.